Pass-through valuation - Robert M. Hull; David P. Price (The Journal of Entrepreneurial Finance (JEF), 2015)
Noted scholars argue that (1) economic models of capital taxation have been inadequately adapted to owner-managed enterprises and (2) capital structure researchers have used the wrong models while also improperly measuring key variables. Thus, a model that can overcome these problems should be of interest to academics when teaching capital structure theory and practitioners when determining optimal debt levels. This paper contributes to capital structure practice by using a model that is adaptable to owner-managed enterprises like pass-throughs while also containing relevant variables that are measurable. This paper should be valuable to academics and practitioners in the following ways. First, we examine the effects of personal tax rates on a pass-through's capital structure choice. Second, we offer rules for managers of pass-throughs on how to choose an optimal amount of debt. Third, we show that increasing market risk by doubling betas does not affect our major conclusions governing a pass-through. Fourth, we compare the pass-through and C Corp gains to leverage values when all factors are the same except tax rates that are unique to the ownership type.
Keywords: C02; G32; M13; 650; Pass-Through Valuation; Tax Rates; Capital Structure Decision-Making